The work in higher education - Deise Mancebo; Kátia Maria Teixeira Santorum; Carla Vaz dos Santos Ribeiro; Denise Bessa Léda (Arizona State University, 2020)
This article presents the dossier, "Work in higher education", composed of 10 articles and discusses the changes that have taken place in the Brazilian labor world since the parliamentary, media and judicial coup that took place in 2016. It considers the hypothesis that one of the central goals of the coup was precisely the attack on work, in distributive sense of income, and also in the organizational sense of social and workers movements. It analyzes the legislation approved in the period - Law 13.429/2017 and Law 13.467/2017 - which has led to a sharp setback in the rights enshrined in the 1988 Constitution, and critically lists the main consequences of this legislation for workers such as unemployment, increased turnover, decrease in wages, reduction of recourses to labor justice and, consequently, increased mockery of protective social legislation at work, weakening of trade union organization and greater suffering at work in general. In the end, it develops the impacts of these changes on the work carried out in higher education institutions.